Novel three-dimensional imaging system may facilitate gastric endoscopic submucosal dissection procedure: an ex vivo animal study - Akizue, Naoki; Matsumura, Tomoaki; Maruoka, Daisuke; Ishikawa, Kentaro; Hang, Dao Viet; Okimoto, Kenichiro; Saito, Keiko; Nakagawa, Tomoo; Arai, Makoto; Kato, Naoya (Endoscopy International Open, 2018)
Background and study aims Endoscopic submucosal dissection (ESD) requires advanced skills to perform safely without complications. The current study evaluated the usefulness of a novel three-dimensional (3D) imaging system in ESD using porcine stomachs.Methods Four endoscopists (two trainees and two experts) performed eight ESD procedures using both 3D and 2D images. The usefulness of 3D image versus 2D image was evaluated by visibility and procedure time. In addition, occurrence of eyestrain and dizziness in 3D image was assessed.Results En bloc resection was successfully achieved, without perforation, in all cases. The evaluation score in the 3D image group was better than that in the 2D image group, particularly depth perception was statistically significantly good. No significant difference was found in the working speed between the 2D and 3D image groups. Two examiners experienced eyestrain and dizziness while using the 3D image.Conclusions All the ESD procedures were performed safely. Depth perception using the 3D image was better than with the 2D image. A novel 3D image system may facilitate ESD.